Friction-induced vibration energy harvesting of a high-speed train brake system via a piezoelectric cantilever beam. (October 2021) - Xiang, Z.Y.; Mo, J.L.; Qian, H.H.; Chen, W.; Luo, D.B.; Zhou, Z.R.
Abstract: Vibration reduction and energy harvesting were achieved by installing a piezoelectric cantilever beam (PZT-beam). Experimental work was carried out on a self-developed tribology and dynamic behavior simulation test device. Finite element (FE) model and numerical simulation model were established to analyze the effect of the PZT-beam on the dynamical response, system stability and the vibration energy harvesting performance of the brake system. The experimental and simulation results show that friction-induced vibration (FIV) can be reduced via a PZT-beam, and the vibration energy can be converted into electrical energy through the deformation of the PZT-beam. The PZT-beam can significantly reduce the real part of the complex eigenvalues of the brake system without significantly changing the unstable vibration frequency and mode shape. Highlights: Vibration reduction and energy harvesting by installing PZT-beam is studied. FIVN test is performed on a self-developed test rig of high-speed train brake system. Mechanism on how PZT-beam affects the stability of brake system is analyzed. FIV energy harvesting performance is discussed via numerical and finite element method.